Branding of Kazakhstani cultural landscape - Povalyashko, G. H.; Khazbulatov, A. R. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
Continuity of history and national identity of Kazakh nation and worldview construct of traditional culture are the most important constituents of new national Kazakhstani mentality. The Eurasian steppes territory is a place of Kazakh nation’s ethno and cultural genesis. The conception of Kazakhstan cultural politics is oriented on the creative projects realization for maintenance and development of country’s cultural heritage. “Branding of territory” is a modern creative technology in a cultural sphere. The main resource of country’s cultural image progress is the resources of culture, which cardinally differentiate it from other territories. The main demand to the branding of territory is a correspondence between the emotional perception of cultural landscape and its factual filling. Some methodological aspects of this issue solution in Kazakhstan are examined in this article